Same or split session concurrent endurance and strength training - effects on strength and muscular power development. A systematic review - Kuronen, S. (Mittuniversitetet (Mid Sweden University), 2020)
Background: Concurrent training of strength and endurance can lead to inferior strength development compared to strength training only. This"interference effect"is most pronounced in those with training experience and a high training volume. The aim of this thesis was to perform a systematic review and meta-analysis to determine the effect of performing endurance and strength training in the same sessions vs. split sessions separated by no more than 12 hours on strength and muscular power development. Method: A searchwas performedforrandomised studies that:-comparedperformingendurance and strength and/or muscular power training in the same session with separate sessions 2-12hours apart-includedparticipants withprevioustraining experience-reportedchanges in maximal isometric or dynamic strength and/or muscularpower. Results: One study matching the inclusion criteria was identified,ameta-analysis was therefore not possible. The identified study found that separating endurance andstrength training by sixhours led to larger improvements in upper and lower body strength development than performing both modalities in the same session. There was no clear difference inlower bodymuscular power.The participants had limitedstrength training experience and the training volume during the intervention was low. Conclusion: More research is needed onhow to plan concurrent training when performed by those with previous training experience in a narrow time frame. The existingevidence, which is of limited applicability to high level athletes,suggests that separating endurance and strength training leads to greaterstrengthdevelopmentthan performing both in a single session.